Merenden Tedong di Mamasa: Integrasi Pendekatan Struktural dan Kultural dalam Memitigasi Konflik Sosial Keagamaan - Bakri, Muhiddin; Mahyuddin; Fitriani; Ariadin, Silmi Qurota Ayun (LP2M IAIN Palopo, 2024)
The Mamasa community has the Merenden Tedong tradition which is rooted in customary law as an effective conflict resolution model in resolving social problems. This tradition is deeply rooted and has become a unique cultural icon in overcoming social challenges and conflicts in society. The integration of this traditional approach with a formal approach from the government has strengthened the mechanism for mitigating socio-religious conflict in social life. This article aims to describe the integration between two conflict resolution models, namely the cultural approach through customary law and the structural approach through government policy, as an effort to mitigate socio-religious conflict in Mamasa. This research used a phenomenological analysis approach involving in-depth interviews. Informants consisted of traditional leaders, community leaders, government officials and community members to gain a comprehensive understanding of the Merenden Tedong tradition as a model for conflict resolution. This research found that the integration of cultural and structural approaches in the Merenden Tedong tradition contributed significantly to mitigating social and religious conflict. Collaboration between traditional institutions and the government strengthened the role of customary law in conflict prevention, proving that an integrative approach is more effective than a unilateral model. Further research is recommended to explore the role of the younger generation in maintaining the identity of Pitu Ulunna Salu as a conflict mitigation strategy. Keywords: Merenden Tedong, Conflict Resolution, Integrative Approach, Mamasa